Socioeconomic Assessment and Impact of Social Security on Outcome in Patients Admitted with Suspected Coronary Chest Pain in the City of Salta, Argentina. (29th May 2013) - León de la Fuente, Ricardo A.; Naesgaard, Patrycja A.; Nilsen, Stein Tore; Woie, Leik; Aarsland, Torbjoern; Staines, Harry; Nilsen, Dennis W. T.
Abstract : Low socioeconomic status is associated with increased mortality from coronary heart disease. We assessed total mortality, cardiac death, and sudden cardiac death (SCD) in relation to socioeconomic class and social security in 982 patients consecutively admitted with suspected coronary chest pain, living in the city of Salta, northern Argentina. Patients were divided into three socioeconomic classes based on monthly income, residential area, and insurance coverage. Five-year follow-up data were analyzed accordingly, applying univariate and multivariate analyses. At follow-up, 173 patients (17.6%) had died. In 92 patients (9.4%) death was defined as cardiac, of whom 59 patients (6.0%) were characterized as SCD. In the multivariate analysis, the hazard ratios (HRs) for all-cause and cardiac mortality in the highest as compared to the lowest socioeconomic class were 0.42 (95% confidence interval (CI), 0.22–0.80), P = 0.008, and 0.39 (95% CI, 0.15–0.99), P = 0.047, respectively. Comparing patients in the upper socioeconomic class to patients without healthcare coverage, HRs were 0.46 (95% CI, 0.23–0.94), P = 0.032, and 0.37 (95% CI, 0.14–1.01), P = 0.054, respectively. In conclusion, survival was mainly tied to socioeconomic inequalities in this population, and the impact of a social security program needs further attention.